Drug effects khat in biocultural and socioeconomic perspective - Gezon, Lisa L. (Advances in critical medical anthropology, 2012)
"Khat, marijuana, peyote--are these dangerous drugs or vilified plants with rich cultural and medical values? In this book, Lisa Gezon brings the drug debate into the 21st century, proposing criteria for evaluating psychotropic substances. Focusing on khat, whose bushy leaves are an increasingly popular stimulant and the target of vehement anti-drug campaigns, she explores biocultural and socioeconomic contexts on local, national, and global levels. Gezon provides a multidisciplinary examination of the plant's direct physical and psychological effects, as well as indirect social and structural effects on income and labor productivity, identity, gendered relationships, global drug discourses, and food security. This sophisticated, multileveled analysis cuts through the traditional battle lines of the drug debate and is a model for understanding and evaluating psychotropic substances around the world"--